The relationship between "Ta'zir" and "forbidding the evil" in Islamic jurisprudence - Mojtaba Javidi; mahdi hamidi (پژوهش‌نامه حقوق اسلامی, 2017)
According to Islamic jurisprudence, "Ta'zir"(discretionary punishment) and "forbidding the evil" are two answers to sin and two strategies for confronting with it. This article seeks for a relationship between this two institutions. Based on the results of this article, there are some commonalities and similarities between them. However, each of them has special features and provisions that necessarily they do not share. The Interpretations of "forbidding the evil", may be broad or narrow and the differences between different interpretations would be effective on the relationship between: ta’zir” and “forbidding the evil”. According to Islamic jurisprudence, the Interpretation of "forbidding the evil" is narrow and does not include "ta'zir" and there is a substantive difference between them. In the terms of Islamic jurisprudence, "Forbidding the evil" is the stage followed by sin, while "Ta'zir" is a kind of punishment and a stage proceeding sin. Absolutely, a behavior can be considered as “forbidding the evil" while it can be taken as "ta'zir" from another perspective. This means that, a behavior is "ta'zir" if its purpose is to deal with the sin committed in the past, and it can be "Forbidding the evil" if the purpose is to prevent the person from repeating the same sin or another sin in the future.